Thermoluminescence dating of ancient toconce potteries - Concha, G.; Roman, A.; Brito, O.; Deza, A. (Ancient TL, 1980)
The dating of five samples from different depth levels of the same archaeological "site” Toconce was made by TL measurements. These results agreed with the estimated values obtained by the archaeological context and the radiocarbon method.